One-pot synthesis of a stable and cost-effective silver particle-free ink for inkjet-printed flexible electronics. Issue 46 (28th October 2020) - Yang, Wendong; Mathies, Florian; Unger, Eva L.; Hermerschmidt, Felix; List-Kratochvil, Emil J. W.
Abstract : A do-it-yourself silver particle-free ink is presented, which shows good stability, low cost and excellent printability. The ink is formulated in selected alcohols. Highly conductive silver patterns were printed on both glass and flexible substrates. Abstract : Silver particle-free inks display immense superiority and potential over silver nanoparticle-based inks in the aspect of synthesis, flexibility and low-temperature processing, which has attracted considerable research interest as an alternative for fabricating conductive structures in recent years. Although recent research on silver particle-free inks has led to beneficial results, there are still some drawbacks: some of the inks are chemically unstable and hence are not suitable for industrial inkjet printing process, although they have good conductivity; while others are cheap in terms of raw material costs but are complicated to make due to the complex synthetic route or using hazardous procedures, or are not compatible with inkjet printing. Therefore, it will be advantageous to develop a stable, cheap and inkjet-printable silver-particle free ink using a simple synthetic procedure. Alcohols are favorable solvents for silver particle-free inks that can provide the ink with essential fluid properties for inkjet printing. However, they have some negative effects on the ink performance due to their physicochemical properties, which should be avoided. In this work, a simple do-it-yourself silver particle-free ink is presented, which shows high chemical stability, low cost and good printability. The ink is formulated via a simple silver oxalate precursor route in alcohols. The fluid property, thermal property, stability and electrical performance of the inks based on different alcohols were investigated and optimized to obtain the final ink for printing on glass and flexible polyimide substrates. The printed Ag features yielded a resistivity of 15.46 μΩ cm at a sintering temperature of 180 °C, which is equivalent to 10 times resistivity of bulk silver. Based on a comprehensive assessment, we can offer a low-cost, easy-to-make, reliable and highly competitive ink for flexible printed electronics.